Circumpolar Information Guide on Mining for Indigenous Peoples & Northern Communities (The Sustainable Development Working Group (SDWG) of the Arctic Council, 2011)
The Circumpolar Information Guide on Mining recognizes that indigenous and northern communities are central stakeholders for a sustainable Arctic. The purpose of the Guide is to increase the ability of Indigenous peoples and residents of northern communities to understand, influence and participate in mining-related processes in order to maximize benefits and minimize negative effects on their lives, culture, land and the environment. Arctic Council's Sustainable Development Working Group